Johnius sasakii, a new species of croaker (Perciformes: Sciaenidae) with a key to Johnius from East Malaysia, Borneo - Hanafi, Norhafiz; Chen, Meng-Hsien; Seah, Ying Giat; Chang, Chih-Wei; Liu, Shang Yin Vanson; Chao, Ning Labbish (Zootaxa, 2022)
A new sciaenid fish, Johnius sasakii sp. nov. from the East Malaysian coastal waters of Sabah and Sarawak, Borneo is described herein. Johnius sasakii sp. nov. can be separated from the close congeners, Johnius heterolepis and Johnius carouna by having less gill rakers on the lower limb of the first gill arch (mode number 9 vs. 10 for J. heterolepis; 11 for J. carouna). It can be distinguished from J. heterolepis with the higher modal number of gill rakers on the upper limb of first gill arch (5 vs. 4), shorter anal-fin base length (9% vs. 10% of SL) and first anal-fin ray length (10–12% vs. 12–13% of SL) respectively. Furthermore, J. sasakii sp. nov. can be further differentiated from J. carouna by its shorter second anal-fin spine length 7–10% SL (usually 8–10%) vs. 11–14% SL (usually 11–12%) and slightly deeper body depth 25–29% SL (usually 26–28%) vs. 23–28% SL (usually 24–26%). Meanwhile, J. sasakii sp. nov. can be easily differentiated from J. macrorhynus by a present of molariform teeth on inner rows of jaws and stumpy gill rakers. Johnius (Johnius) sasakii sp. nov. can be clearly distinguished from species of the subgenus J. (Johnieops) by the lack of enlarged outer row teeth on upper jaw. A Kimura 2-parameter genetic distance comparison of 450 bp sequences of mitochondrial 16S rRNA and 488 bp nuclear gene S7 showed that J. sasakii sp. nov. are highly differentiated from J. heterolepis (16S: 10.4%, S7: 5.8%), J. carouna (16S:19.3%, S7:8.4%); and J. macrorhynus (16S: 16.7%, S7: 8.1%) respectively. The study highlights that the genetic approach from mtDNA and nDNA can contribute to the confirmation of taxonomic status of sympatric species in genus Johnius.